GENERAL CONCEPT OF THE POSITIVE IMPACT AND CRITERIA OF THE SCIENCE OF LIFE ACTIVITY SAFETY ON HUMAN LIFE - Berdirasulov Dilshod Qodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
The sum of active actions of a person means the concept of activity. It is this activity that distinguishes humans from other living creatures. Therefore, activity is a necessary indicator for the existence of a person. Labor is the highest form of human activity. Therefore, if there is no activity and labor, there will be no human society. Vital activity is a person's daily activities, rest, and lifestyle.